The Heliand Translated from the Old Saxon - Scott, Mariana (UNC Studies in the Germanic Languages and Literatures, 1966)
Mariana Scott, poet and translator of Hofmannsthal, Meyrink, Celan, and others, translates the eight-century Old Saxon Heliand into its original meter in this work originally published in 1966. This anonymous masterpiece presents the life of Christ and affords an excellent insight into medieval life.